THE STUDY OF THE STRIPPING PROPERTIES OF BITUMINOUS MIXTURES CONTAINING DIFFERENT AGGREGATE TYPES - HUSSEIN ELHASSAN, MOHAMED SALAHELDIN (IRC, 2016)
This report present an experimental study to establish the properties of stripping in the bituminous mixtures by using different types of aggregates. Two types of aggregate were used with varying chemical and moisture sensitivity characteristics. Stripping is considered as a common issue that is caused from water exposure to the highway pavement that might lead to different issues such as fatigue and traffic damages. Such issues will lead to full repair of the damaged area, which is very costly, therefore a correct material selection is vital to obtain a good quality of highway pavement that is more resistant to stripping.